CD8+ Regulatory T Cell – A Mystery to Be Revealed - Mishra, Shruti; Srinivasan, Saranya; Ma, Chaoyu; Zhang, Nu (Frontiers in Immunology, 2021)
Regulatory T cells (Treg) are essential to maintain immune homeostasis and prevent autoimmune disorders. While the function and molecular regulation of Foxp3+CD4+ Tregs are well established, much of CD8+ Treg biology remains to be revealed. Here, we will review the heterogenous subsets of CD8+ T cells have been named “CD8+ Treg” and mainly focus on CD122hiLy49+CD8+ Tregs present in naïve mice. CD122hiLy49+CD8+ Tregs, which depends on transcription factor Helios and homeostatic cytokine IL-15, have been established as a non-redundant regulator of germinal center (GC) reaction. Recently, we have demonstrated that TGF-b (Transforming growth factor-b) and transcription factor Eomes (Eomesodermin) are essential for the function and homeostasis of CD8+ Tregs. In addition, we will discuss several open questions regarding the differentiation, function and true identity of CD8+ Tregs as well as a brief comparison between two regulatory T cell subsets critical to control GC reaction, namely CD4+ TFR (follicular regulatory T cells) and CD8+ Tregs.